The Role of EjSOC1s in Flower Initiation in Eriobotrya japonica - Jiang, Yuanyuan; Peng, Jiangrong; Zhu, Yunmei; Su, Wenbing; Zhang, Ling; Jing, Yi; Lin, Shunquan; Gao, Yongshun (Frontiers in Plant Science, 2019)
The MADS-box transcription factor SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1) integrates environmental and endogenous signals to promote flowering in Arabidopsis. However, the role of SOC1 homologs in regulating flowering time in fruit trees remains unclear. To better understand the molecular mechanism of flowering regulation in loquat (Eriobotrya japonica Lindl.), two SOC1 homologs (EjSOC1-1 and EjSOC1-2) were identified and characterized in this work. Sequence analysis showed that EjSOC1-1 and EjSOC1-2 have conserved MADS-box and K-box domains. EjSOC1-1 and EjSOC1-2 were clearly expressed in vegetative organs, and high expression was detected in flower buds. As observed in paraffin-embedded sections, expression of the downstream flowering genes EjAP1s and EjLFYs started to increase at the end of June, a time when flower bud differentiation occurs. Additionally, high expression of EjSOC1-1 and EjSOC1-2 began ten days earlier than that of EjAP1s and EjLFYs in shoot apical meristem (SAM). EjSOC1-1 and EjSOC1-2 were inhibited by short-day (SD) conditions and exogenous GA3, and flower bud differentiation did not occur after these treatments. EjSOC1-1 and EjSOC1-2 were found to be localized to the nucleus. Moreover, ectopic overexpression of EjSOC1-1 and EjSOC1-2 in wild-type Arabidopsis promoted early flowering, and overexpression of both was able to rescue the late flowering phenotype of the soc1-2 mutant. In conclusion, the results suggest that cultivated loquat flower bud differentiation in southern China begins in late June to early July and that EjSOC1-1 and EjSOC1-2 participate in the induction of flower initiation. These findings provide new insight into the artificial regulation of flowering time in fruit trees.